Analysis of Occupational Therapy In Schizophrenic Patients - Siti Khadijah; Darni Darni; Sitti Sulaihah (Jurnal Ners, 2019)
Nursing care in the rehabilitation phase is one which provides occupational therapy, which is one form of combination therapy between art and science to direct patients to selective activities, so that health can be improved and maintained, and prevent disability through work activities and training This study is to show evidence of the effectiveness of occupational therapy interventions: job training in schizophrenic patients at the Mental Hospital.Methods: The method used in this systematic review consists of 5 stages: identification of instruments in the literature (database search); identification of relevant literature based on title and abstract; inclusion and exclusion criteria; obtaining full text literature; assessment based on literature component and analysis of selected instruments. The database used in the literature search was Scopus, Proquest, Science Direct, Japan Journal, Cochrane by limiting the keywords "Occupational Therapy" and "Schizophrenia", which were published in the years between 2012-2018.Results: Fifteen studies were included in the analysis, only 10 journals met the criteria to be included in the quantitative design.Conclusion: From the results of this study it was found that occupational therapy was significant in improving cognitive, social, work, welfare, and contributing to the quality of life of patients.